A proposed classification schedule for University of the Philippines publications based on the Library of Congress Classification Scheme - Aguirre, Vyva Victoria M.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1975)
This paper is a major revision of the UPIANA scheme, a classification schedule developed by previous librarians of the Cataloging Department, University of the Philippines Library, for use in the classification of U.P. publications. It aims to develop a more comprehensive and more flexible scheme, using the present UPIANA scheme as a frame of reference.
A survey of the UPIANA collection, was, therefore, made in order to get a sampling of the type of materials which will be classified with proposed scheme. The Library of Congress schedules for individual institutions, particularly for Harvard and Yale, and the Joseph Cummings Rowell Classification for Printed Materials in the Archives of the University of California at Berkeley, were likewise examined and compared. Then the numbers assigned for the classification of UPIANA (LG995-999) were divided in logical sequence, using the different U.P. catalogs and other official publications as references. The tables of subdivisions by colleges, units departments and officers and various degrees offered in the graduate program were also expanded and revised to include most recently created offices and departments of the University and changes in names of the same. Aside from the expansion made in the schedule and tables of subdivisions, a major revision will be noted in the system used for subdividing broad topics. Whereas the present schedule uses the successive cuttering from A1-5, the proposed scheme makes use of decimals in order to allow more flexibility. A change in the use of Table I (Departments of Instruction and Graduate Degrees Offered) was also made for the classification of course papers, theses and dissertations. Instead of subdividing them by departments of instruction, they are now subdivided by degrees conferred or by major courses. A more generous use of explanatory and instruction notes is also made throughout the proposed schedule to avoid confusion in classifying certain materials. It is hoped that this endeavor would result in the improvement of the classification of the UPIANA collection and contribute to the development of library service. It could perhaps serve as a guide for the organization of other special collections.
Appendices: p. 45-64.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Classification